Becoming a mother when suffering from a chronic illness - Riazuelo, Hélène (Frontiers in Psychiatry, 2023)
Introduction The critical period of early motherhood when facing serious health problems constitutes a major public health issue. The disease may interfere with, influence, and compound the difficulties experienced over the course of pregnancy and during the parenthood processes. These processes are to be understood as a passage involving so many changes and fraught with difficulties leading to a series of psychological mobilizations. Illness also needs to be considered as a moment of transition, sometimes of severance, marking the lives of the people concerned in a more or less lasting way. Various developments are possible, some of which can be envisaged as leading to more positive outcomes, while others appear as if blocked or doomed to failure. Clinical data and method This clinical study is the result of twelve analytically oriented psychotherapeutic follow-ups. The sessions took place weekly over periods ranging from 1 to 6 years. Some of the patients we met had become pregnant while they had a declared but not yet chronic nephropathy. The other patients were already on dialysis and had become mother before starting dialysis. There is also one instance of a pregnant patient on dialysis. In the background, there are also many women who talked about giving up fertility and motherhood. After an in-depth study of each follow-up, a cross-sectional study was conducted to identify the main themes. Results and discussion Main considerations on the psychotherapeutic treatment: We regularly observe people who find it impossible to muster the internal resources that would enable them to deal with the trials they undergo in such situations. For the psychologist, there is a need to listen to archaic remnants. Gradually, in the space of psychotherapeutic work, possibilities of “reanimation” of the psyche emerge, an internal space that renews fantasmatic activity as it begins to be able to project into the external space and into the space of the sessions.